Safety Challenges and Application Strategies for the Use of Dendrimers in Medicine - Xiang Li; Abid Naeem; Shanghua Xiao; Lei Hu; Jing Zhang; Qin Zheng (MDPI AG, 2022)
Dendrimers are used for a variety of applications in medicine but, due to their host-guest and entrapment characteristics, are particularly used for the delivery of genes and drugs. However, dendrimers are intrinsically toxic, thus creating a major limitation for their use in biological systems. To reduce such toxicity, biocompatible dendrimers have been designed and synthesized, and surface engineering has been used to create advantageous changes at the periphery of dendrimers. Although dendrimers have been reviewed previously in the literature, there has yet to be a systematic and comprehensive review of the harmful effects of dendrimers. In this review, we describe the routes of dendrimer exposure and their distribution in vivo. Then, we discuss the toxicity of dendrimers at the organ, cellular, and sub-cellular levels. In this review, we also describe how technology can be used to reduce dendrimer toxicity, by changing their size and surface functionalization, how dendrimers can be combined with other materials to generate a composite formulation, and how dendrimers can be used for the diagnosis of disease. Finally, we discuss future challenges, developments, and research directions in developing biocompatible and safe dendrimers for medical purposes.